Pedagogical aspects of students' digital competence development - Demchyk, Kateryna; Pasichnyk, Mykola; Pozharytska, Olena; Парфенюк, Ігор; Tonkykh, Oleksii (Editorial Authors and Associated Researchers, 2021)
The purpose of the research was to study the pedagogical aspects of students’ digital competence development and the degree of teachers’ encouragement to develop their own professional digital competence. The study is based on quantitative and qualitative methodology and contains an online structured interview of 132 teachers of Ukraine who took an online course on the development of digital competencies. Results. University teachers demonstrated different beliefs and effectiveness in the use of ICT for pedagogical purposes. Although a few teachers seamlessly integrated ICT into the learning process, most were more tool-oriented and supported a teacher-rather than student-centered approach when designing online courses. In a pandemic, teachers are massively interested in the development of digital competence as part of professional development. At the same time, the strategy of the university and the practice of functioning of the university testify to the lack of a course for the implementation of absolute digital pedagogy.
Aspectos pedagógicos do desenvolvimento de habilidades digitais dos alunos
https://doi.org/10.24115/S2446-622020217Extra-A848p.471-480
Keywords: digital competence; pedagogical preconditions of digital competence; online learning programs; innovative teaching methods